Research tools for the development of human capital international companies - Zafirov, Martin (Leadership, Society, Strategic Visions, 2021)
A major feature of modern society is the enhanced process of globalization and international cooperation. These relationships are becoming increasingly complicated, which complication itself results in the need for better and more adequate management of the different types of resources in an economic system. This applies equally to human capital, especially to this human capital in transnational corporations. The article summarizes the basic tools and results of a study of evolution in the understanding and management of human capital in transnational corporations in the Persian Gulf, as well as the impact that cultural differences have on these processes.